Fully-Depleted SOI MOSFET Sensors in Accumulation Mode for Total Dose Measurement - Alcalde Bessia, F.; Flandre, D.; André, N.; Irazoqui, J.; Pérez, M.; Gómez Berisso, M.; Lipovetzky, J. (IEEE (Institute of Electrical and Electronics Engineers), 2018)
Fil: Alcalde Bessia, F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina